A novel methodology for the treatment of the 𝛾-flash for fission experiments with Micromegas at EAR1 of n_TOF (CERN). - Kyritsis, Nikolaos; Diakaki , Maria; Michalopoulou , Veatriki; Eleme , Zinovia; Kokkoris , Michael; Nicolis, Nikolaos; Patronis , Nikolaos; Vlastou , Roza; n_TOF collaboration, (HNPS Advances in Nuclear Physics, 2026)
The study of neutron induced fission reactions in major and minor actinides is an ongoing effort, important both for the development of advanced nuclear systems, such as Generation IV reactors and accelerator driven systems and for basic research on the fission process. As part of this effort an new measurement of the 243Am (n,f) reaction cross-section took place at the n_TOF facility (CERN) to provide data from thermal neutrons up to hundreds of MeV. In this work a novel method for the treatment of the 𝛾-flash in EAR1 of the n_TOF facility has been developed in order to extend the upper limit of the measured neutron energies. This approach has been experimentally tested using the reference targets of the 243Am measurement, 235U and 238U, to show the maximum neutron energy that can be measured with this setup. The results of this analysis are presented here.